Dystocia due to Fetal Malposture in a Jenny: A Case Report - Solanki, GB; Parmar, KH; Naval, RJ; Vala, KB; Odera, MD (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Reproductive aspect of Jenny is very similar to that of Mare being that they both belong to the same genus Equus. The average length of gestation in donkeys varies between 10½ to 14½ months (Kirby, 1989). Dystocia is defined as any birth that reduces neonatal viability, causes maternal injury or requires assistance (Purohit and Honnappagole, 2009). Dystocia is much more common in primipara than pluripara (Roberts, 1986). Dystocia in Jenny can be caused by abnormalities of either maternal or foetal origin. In view of above facts a case of dystocia in Jenny due to right lateral deviation of fetal head with flexed left shoulder and its delivery by mutation is placed on record.